The place of intelligentsia in socio-economic development of society: the creative perspective - Tabeikyna, Elena K.; Kamalova, Galina T.; Hasanov, Elnur L.; Dzhumagaliyeva, Kulyash V.; Demeuova, Nurgul K. (Creativity Studies, 2021)
In the context of the socio-economic approach to determining the place and role of the intelligentsia and its interaction with authorities, often only one point is reviewed, in which the intelligentsia is defined as the most progressive layer of society and at the same time oppressed by the authorities for progressive views. Thus, a search is needed between the desire of society for progress and the search for optimal conditions for coexistence between power and the intelligentsia. The novelty of the work is determined by the fact that the historical basis of the interaction between government and the intelligentsia should be considered not only in a historical perspective but also on the basis of an economic or anthropological approach. The authors of the article determine the role economic nature of the intelligentsia in the positive development of a socio-economic nature in society. The practical significance of the study is determined by the possibility of forming social development programs on the basis of philosophical discussions and determining the place and role of the intelligentsia in social development.